Twenty years of anastomotic stenosis combined with tracheocolonic fistula after colon replacement esophagectomy: a case report - Li, Xiaofang; Zou, Liutao; Shi, Lifeng; Zheng, Xueting; Xu, Cuifang; Guo, Jichao (Frontiers in Oncology, 2024)
Esophageal stricture is the most common and disabling complication of esophageal injury caused by ingestion of corrosive substances. In our case, the patient developed esophageal stenosis due to ingestion of strong alkaline substances and underwent colon replacement surgery after repeated failed dilation treatments. After surgery, anastomotic stenosis and tracheocolonic fistula occurred successively, and the entire diagnosis and treatment cycle of this disease lasted for more than 20 years. Based on experience and the actual situation of the patient, we conclude that esophageal stents should be the primary treatment option, while tracheal stents should be carefully selected, and secondary surgery is not recommended.